Detection of First Marker Trait Associations for Resistance Against Sclerotinia sclerotiorum in Brassica juncea–Erucastrum cardaminoides Introgression Lines - Rana, Kusum; Atri, Chhaya; Akhatar, Javed; Kaur, Rimaljeet; Goyal, Anna; Singh, Mohini Prabha; Kumar, Nitin; Sharma, Anju; Sandhu, Prabhjodh S.; Kaur, Gurpreet; Barbetti, Martin J.; Banga, Surinder S. (Frontiers in Plant Science, 2019)
A set of 96 Brassica juncea – Erucastrum cardaminoides introgression lines (ILs) were developed with genomic regions associated with Sclerotinia stem rot (Sclerotinia sclerotiorum) resistance from a wild Brassicaceous species E. cardaminoides. These were assessed for their field resistance responses to S. sclerotiorum, over three seasons (season I, 2011/2012; II, 2014/2015; III, 2016-17). Initially, ILs were genotyped with transferable SSR markers and subsequently through genotyping by sequencing. SSR based association mapping identified six marker loci on each of A and B genomes. Subsequent genome wide association analysis (GWAS) of 84 ILs recognized a large number of SNPs, on chromosomes A03, A06, B02 and B03. Chromosomes A03 and A06 harbored the maximum number of sclerotinia related SNPs. Annotation of linked genomic regions highlighted an array of resistance mechanisms in terms of signal transduction pathways, hypersensitive responses and production of anti-fungal proteins and metabolites. Of major importance was the clustering of SNPs, encoding multiple resistance genes on small regions spanning approximately 885 kb region on chromosome A03 and 74 kb on B03. Six SNPs on chromosome A03 (6390210-381) and one on B02 (B02_13915123) were associated with LRR-RLK (receptor like kinases) genes that encode LRR-protein kinase family proteins. Genetic factors associated with pathogen-associated molecular patterns (PAMP) and effector-triggered immunity (ETI) were identified on chromosome A03, exhibiting 11 SNPs (6274763-994) belonging to three R-Genes encoding TIR-NBS-LRR proteins. Marker trait associations (MTAs) identified will facilitate marker assisted introgression of these critical resistances, into new cultivars of B. juncea initially and, subsequently, into other crop Brassica species.